The Analysis of Carrying Capacity toward the Sustainable Development of Pentingsari Tourism Village, Sleman Regency - Yulaichah, Yulaichah; Umaroh, Rokhmatul; Afiyah, Zakiyatul; Muta'ali, Lutfi (TEHBMJ (Tourism Economics Hospitality and Business Management Journal), 2025)
The tourist village of Pentingsari encounters challenges due to rapid growth into a national and international tourist destination. The major issue is the tourist flow management to prevent exceeding the rate against the social capacity and the village. The concept of carrying capacity becomes a crucial matter in this context. This research attempts to find the physical carrying capacity (PCC), real carrying capability (RCC), and effective carrying Capacity (ECC) of the Pentingsari Tourism Village; to make an estimated rate of tourist visits in Pentingsari Tourism Village; to provide advice for sustainable tourism management strategies based on the findings of the support capability analysis. This mixed research method research applied primary and secondary data sources. The results found that the PCC, RCC, and ECC calculations and projections of the number of visits to the Pentingsari Tourist Village from 2028 to 2048 were still acceptable. However, further monitoring of the environmental sustainability is important. Therefore, the management strategy recommendation is important for the village by considering the economic, environmental, and social-cultural aspects to ensure sustainable tourism development.